201k views
0 votes
Step 1: m∠x + m∠y + m∠z = 180 degrees (sum of angles of a triangle) Step 2: m∠w − m∠z = 90 degrees (corresponding angles) Step 3: Therefore, m∠x + m∠y + m∠z = m∠w + m∠z Step 4: So, m∠x + m∠y = m∠w

User VPNTIME
by
5.3k points

2 Answers

2 votes

Answer:

Step 1

Explanation:

User Hyque
by
5.3k points
1 vote

Step 1: m∠x + m∠y + m∠z = 180 degrees (sum of angles of a triangle) Step 2: m∠w − m∠z = 90 degrees (corresponding angles) Step 3: Therefore, m∠x + m∠y + m∠z = m∠w + m∠z Step 4: So, m∠x + m∠y = m∠w

User XKxAxKx
by
6.1k points